Should the nail plate be replaced or discarded after nail bed repair in children? Nail bed INJury Analysis (NINJA) randomised controlled trial: a health economic and statistical analysis plan - Stokes, JR; Png, ME; Jain, A; Greig, AVH; Shirkey, BA; Dritsaki, M; Cook, JA (BioMed Central, 2020)
BACKGROUND: Nail bed trauma is one of the most common surgically treated paediatric hand injuries in the UK. Despite surgeons generally expressing a preference to replace the nail plate after repairing the nail bed, there is limited evidence to support this practice. We describe a statistical and health economic analysis plan (SHEAP) for the Nail bed INJury Analysis (NINJA) randomised controlled trial. METHODS/DESIGN: NINJA is a multicentre, pragmatic, superiority, parallel group randomised controlled trial of the treatment of nail bed injury in participants 16 years old or younger. The study aims to evaluate the efficacy and cost-effectiveness of replacing the nail plate compared to discarding it following the repair of a nail bed injury. Surgical site infection at 7-10 days post-randomisation and cosmetic appearance of the nail are the co-primary outcomes for NINJA. Surgical site infection at 7-10 days post-randomisation will be evaluated using a logistic regression model adjusting for site as the sole stratification factor and allowing for intra-site correlation. Cosmetic appearance will be assessed via the newly developed Oxford Finger Nail Appearance Score and will be evaluated by use of a Mann-Whitney U test. An ordinal logistic regression model will also be used to assess the Oxford Finger Nail Appearance Score, adjusting for site and allowing for intra-site correlation. Secondary outcomes are measured at 7-10 days and 4 months and include the EQ-5D-Y questionnaire, pain at first dressing change, cost-effectiveness, late surgical site infection, and participant/parent satisfaction with nail healing. Missing primary outcome data will be summarised by treatment arm and investigated through a sensitivity analysis. Full details of the planned methods of analysis and descriptive statistics are described in this paper. The NINJA study protocol has been published previously. DISCUSSION: The planned analysis strategy for the NINJA trial has been set out here to reduce the risk of reporting bias and data-driven analysis. Any deviations from the SHEAP described in this paper will be detailed and justified fully in the final report of the trial. TRIAL REGISTRATION: ISRCTN, ISRCTN44551796 . Registered on 23 April 2018.